The antinociceptive and spinal cord histopathologic effects of intrathecal tramadol administration in the rat [Siçanlarda uygulanan intratekal tramadolün analjezik ve nörohistopatolojik etkileri] - (:unkn) unknown (Turkish Society of Algology, 2002)
This study was designed to determine the antinociceptive and spinal cord histopathologic effects of intrathecal tramadol administration. 8 Wistar rats receiving intrathecal (i.t.) tramadol (10 μg) for 5 days (tramadol group) were compared with a control group of 8 rats receiving i.t. saline. Antinociceptive activity was evaluated using hot-plate (cutaneous thermal) and writhing (visceral chemical) tests. Light microscopy study was performed on cervical, thoracic and lumbar sections of the spinal cord to investigate possible tramodol induced neurotoxic effects. Mean hot plate latencies were 51.2s (±10.1) in the tramadol group and 19.7s (±5 5) in the control group (p<0.001). Cumulative writhing scores in 15 to 50 min after intrathecal injections were also significantly lower in the tramadol group than in the control group (p<0.05). Light microscopy study did not show any morphological changes suggestive of tramadol induced neurotoxicity when compared with similar preparations obtained from controls.
Keywords: Antinociceptive effect; Histology; Intrathecal; Spinal cord; Tramadol